VALIDITY OF THE ACCOUNTING METHOD TO APPRAISE THE ASSETS OF SMES - Salazar Frisancho, Ángel Roberto (2016)
This paper presents and systematizes the grounds of accounting method for the appraising of SMEs, in an analytical and synthetic way, according to their sequences it is also disclosed the way to use the accounting method to value the assets of the companies -by the accounting professional- taking into consideration the adjustments of the of assets ́ value in applying the international accounting standards relating to SMEs and the intangibles.The accounting method for valuing company assets has the feature of mobilizing all knowledge of the accounting discipline. This method puts into action the principles, rules, procedures and accounting techniques in order to appraise the assets of a company. The set of identified knowledge is taught in the professional training of the accountant, which predisposes and prepares this professional for the use of knowledge acquired as a method of valuing the assets of the companies.Finally, it is concluded that there is a validity and recognition of the general accounting method for valuing the assets of companies, and by other methods as a reference.